Leitura de poesia no 9º ano do ensino fundamental : um caminho rumo ao letramento lírico - Almeida, Adilson Oliveira (2018)
Poetry and literature as a whole have been marginalized and discredited in Portuguese language classes in elementary school. Reading poetry and lyrical literacy are essential for students at this level of basic education to apply and make good use of their knowledge in various social contexts. In addition, working with the poem genre and / or other texts that retake poetic language is very enriching for the student, since with these textual genres in the classroom and at school the student is allowed to reach a substantial level of humanization, awareness and reflection on the culture and legacy of a people, and their own history in the world. The main objective of this initiative was to equip students for lyric literacy by reading poems and poetic language texts. The pedagogical intervention that gave rise to this academic report was held in Class A of the 9th year of elementary school, at the José de Alencar Cardoso State School, located in Aracaju / SE. For this purpose, questionnaires were applied before and during the activities with the corpus, whose purpose was to seek to know what the students knew or did not know and / or what they learned about poetry and poetry. The didactic activities were given dynamically, with silent, oral, expressive, analytical and interpretive readings. The corpus used in this research consisted of two chronicles and three poems. As a theoretical contribution, we are based on Rildo Cosson (2014); Neusa Sorrenti (2013), Octavio Paz (2012); Tzvetan Todorov (2009); Antonie Compagnon (2010 and 2012); Egon Rangel (2003); Antonio Candido (1987); Regina Zilberman (2009), Hélder Pinheiro (2007); Fernando Paixão (1983); Massaud Moisés (2007); Emil Staiger (1977), among other authors.